The Evolution of Competitive Strategies in Global Forestry Industries Comparative Perspectives - Lamberg, Juha-Antti.; Näsi, Juha.; Ojala, Jari.; Sajasalo, Pasi.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
This book presents an analysis of the evolution of competitive strategies within the forestry industry. Although the discussion takes place in a relatively narrow field of business on the global scale, the argument is that the chosen context serves as an illustrative setting for a discussion related to global corporate evolution of firms since the industry studied has only recently entered a stage of development characterized by intensified global competition. Moreover, the global forestry industry provides also an ideal setting for the analysis of the changing dynamics of competition within an industry. We propose that the development within the studied industry serves as a symptomatic illustration of the ongoing development processes in other industries: from a competitive setting characterized by a number of small competitors to one dominated by few large equally strong competitors aiming for a global presence. The implications of the study are not restricted to the forestry industry context alone. They extend to other manufacturing industries displaying similar features to the industry studied: maturity, commodity nature, fragmented industry structure, lack of industry leader, and ongoing concentration process. Thus, our contention is that this book contributes to better understanding of the workings of a number of manufacturing industries through discussion of the evolutionary development within the pulp and paper industry.
I -- Evolution of Competitive Strategies in Global Forestry Industries: Introduction -- II -- The Giant: International Paper 1898–2000 -- A Company and the State: Enso-Gutzeit -- Comparing the Strategic Evolution of Georgia-Pacific, Mead and Weyerhaeuser -- The Challengers: Kymmene, United Paper Mills, and Metsäliitto -- Strategy Formation in the Swedish Forestry Industry: Comparing SCA and MoDo -- Two Family Firms in Comparison: Ahlström and Schauman During the 20th Century -- Entrepreneurial Organization or Family Firm? A Strategic Analysis of Gulf States Paper Corporation -- III -- Managerial Cognition and Action in the Context of the Forestry Industry -- Consolidation by Game-Playing: a Gamesmanship Inquiry into Forestry Industry -- IV -- The Ephemera of Success: Strategy, Structure and Performance in the Forestry Industries.
Keywords: Agricultural economics; Forestry; History; Business; Management science; Industrial organization; Agricultural Economics; Forestry; History, general; Business and Management, general; Industrial Organization